Residents’ Satisfaction and Support to Sustainable Tourism Development: Evidence from Tra Vinh Province, Vietnam - Huynh, Quang Linh (Asian Journal of Empirical Research, 2018)
This research attempts to evaluate local residents’ satisfaction and support to the development of tourism through economic, environmental and socio-cultural sustainability of tourism. The data was collected with a survey of local residents in Tra Vinh province of Vietnam. The empirical findings demonstrate that local residents’ perceived economic, environmental and socio-cultural sustainability affects both their satisfaction and support to tourism development in the locality. The sustainability of socio-culture is most concerned by local residents. The greatest importance is, this research discussed and offered statistical evidence on the mediating role of local residents’ satisfaction with the development of tourism in the effect of perceived economic, environmental and socio-cultural sustainability on local residents’ support to the development of local tourism. The current study is expected to provide tourism managers with a better understanding of the complicated links among economic, environmental, socio-cultural sustainability, local residents’ satisfaction and their support to tourism development. Therefore, they should pay more attention to tourism satisfaction of local community in order to enhance host residents’ support to the development of local tourism.